Experiences and perceptions of participants on the pathway towards clinical management of dual tuberculosis and diabetes mellitus in Tanzania. Issue 1 (31st December 2022) - Chamba, Nyasatu G.; Byashalira, Kenneth C.; Christensen, Dirk L.; Ramaiya, Kaushik L.; Kapyolo, Eliakimu P.; Shayo, PendoMartha J.; Lillebaek, Troels; Ntinginya, Nyanda E.; Mmbaga, Blandina T.; Bygbjerg, Ib C.; Mpagama, Stellah G.; Manongi, Rachel N.
ABSTRACT: Background: Diabetes mellitus (DM) is a common comorbidity among people with tuberculosis (TB). Despite the availability of guidelines on how to integrate dual TB/DM in Tanzania, the practice of integration at various healthcare levels is unclear. Objective: To explore the participants' experiences and perceptions on the pathway towards clinical management of dual TB/DM. Method: The research was carried out in Dar es Salaam, Iringa, and Kilimanjaro regions between January and February 2020. A qualitative, in-depth interview approach was used to collect participants' experiences and perspectives on the acquisition of dual TB/DM services at various levels of healthcare facilities. The information gathered were coded and classified thematically. Results: The participants' perception of TB services within the healthcare facilities was positive due to the support they received from the healthcare providers. On the other hand, participants reported difficulty receiving management in various health facilities for each condition in terms of access to dual TB/DM care and access to DM medication. This was viewed as a significant challenge for the participants with dual TB/DM. Conclusions: The current disjunction and disruption in healthcare for people with dual TB/DM makes it difficult to access services at various levels of health facilities. For optimal clinical management for people with dual TB/DM, patient-centered strategies and integrated approaches are urgently needed.